INDONESIAN DIASPORA IN THE UNITED STATES. STUDY OF SOCIAL MEDIA IN PUBLIC DIPLOMACY'S SELF-IMAGE - Azahra Shafa Nabila; Surwandono Surwandono (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
This article aims to understand how the Indonesian diaspora conveys their experiences and knowledge in dealing with sociocultural and economic differences, as well as American immigration policies that are becoming less and less welcoming to immigrants.  This study analyzed the content of 100 videos produced by the Indonesian diaspora in America using coding methods based on four main categories: “Survival in America”, “Working Professionally in America”, “Tips for Facing Problems in America”, and “Adapting to a New Environment in America”. The results of the study show that the majority of videos talk more about how to live comfortably in America by becoming a legal immigrant. Topics such as legal pathways to obtaining residence permits, successful strategies for working professionally, and adaptation to American social and cultural norms become dominant in the narratives constructed by the diaspora. The main focus of this diaspora public diplomacy is to provide practical education for Indonesians who want to or have lived in the United States so that they can integrate well and minimize risks related to immigration status.